Answer:
D. x = 1.2
Step-by-step explanation:
A value of x is a solution of the equation if when we replace, x by the given value, the equation is satisfied.
Therefore, for each option we get:
A. Replacing x = -6, we get:
5x² - 36x + 36 = 0
5(-6)² - 36(-6) + 36 ≠ 0
5(36) + 216 + 36 ≠ 0
180 + 216 + 36 ≠ 0
432 ≠ 0
Then, x = -6 is not a solution of the equation
B. Replacing x = 4, we get:
5x² - 36x + 36 = 0
5(4)² - 36(4) + 36 ≠ 0
5(16) - 144 + 36 ≠ 0
80 - 144 + 36 ≠ 0
-28 ≠ 0
Then, x = 4 is not a solution of the equation
C. Replacing x = -1.8, we get:
5x² - 36x + 36 = 0
5(-1.8)² - 36(-1.8) + 36 ≠ 0
5(3.24) + 64.8 + 36 ≠ 0
16.2 + 64.8 + 36 ≠ 0
117 ≠ 0
Then, x = -1.8 is not a solution of the equation
D. Replacing x = 1.2, we get:
5x² - 36x + 36 = 0
5(1.2)² - 36(1.2) + 36 = 0
5(1.44) - 43.2 + 36 = 0
7.2 - 43.2 + 36 = 0
0 = 0
Then, x = 1.2 is a solution of the equation
Therefore, the answer is x = 1.2